Dose-Dependent Effects of Histamine on Growth, Immunity and Intestinal Health in Juvenile Grouper (Epinephelus coioides) - Liu, Zi-Yan; Yang, Hong-Ling; Hu, Ling-Hao; Yang, Wei; Ai, Chun-Xiang; Sun, Yun-Zhang (Frontiers in Marine Science, 2021)
A 56 day feeding trial was conducted to examine the effects of different levels of dietary histamine on growth performance, immune response, and intestinal health of grouper (Epinephelus coioides). Seven isonitrogenous (46%), isolipidic (10%) diets were prepared with histamine supplement levels of 0 (T0), 0.05% (T1), 0.1% (T2), 0.15% (T3), 0.2% (T4), 0.25% (T5), and 0.3% (T6), respectively. The results showed that histamine supplementation had no significant effects on weight gain rate (WGR), specific growth rate (SGR), feed conversion rate (FCR), hepatosomatic index (HSI), and survival rate (SR) at the initial feeding period (day 0–28), but WGR and SGR had negative linear responses to the dietary histamine level at the whole feeding period (day 0–56), and a significant decrease was observed in groups T5 and T6 compared with T0 (P < 0.05). Supplementation of histamine decreased antioxidant capacity, immune response, the contents of serum interleukin-1 beta (IL-1β), intestinal-type fatty acid-binding protein (FABP2) and intestinal trefoil factor (ITF), and caused serious damage of intestine with significantly decreased VH and MFH of grouper, especially in fish fed with diets supplemented with high doses of histamine (0.25 and 0.3%). The intestinal microbial communities in treatments were different clearly with the control (T0), in terms of beta (β)-diversity boxplots and UPGMA phylogenetic tree based on unweighted unifrac distance. At the phylum level, the relative abundance of Fusobacteria was lower in group T0, while the abundance of Firmicutes was significantly lower in groups T5 and T6 (P < 0.05). At the genus level, the relative abundance of uncultured_bacterium_f_Bacteroidales_S24-7_group, uncultured_bacterium_f_Lachnospiraceae, and Ruminiclostridium were significantly higher in the control, while the abundance of Cetobacterium was significantly higher in groups T5 and T6 (P < 0.05). In conclusion, the present study suggested that up to 0.2% of dietary histamine did not result in a remarkable reduction in growth, immune response, and intestinal health; however, 0.25% or more dietary histamine could cause significant negative effects on growth performance, immune response, and intestinal health in E. coioides.